Deceptive Dynamics in Drug Addiction and Their Role in Control Beliefs and Health Status Reporting: A Study on People With Substance Use Disorder in Treatment. (October 2019) - Caputo, Andrea
This study aims at exploring deceptive dynamics (i.e., impression management [IM], self-deception, and emotional manipulation [EM]) and their role in control beliefs and health status reporting in a sample of people treated for substance use disorder. Seventy-eight participants following drug rehabilitation treatment were recruited, who provided background information and completed measures of social desirability responding, EM, locus of control, and health-related status. Moderated-regression analyses and t tests were performed. The results highlight that self-deception is associated with not reporting the use of secondary substances and being in treatment for a shorter time period. IM appears as the main deceptive tendency able to account for internal control beliefs and better mental health. Some interaction effects emerge among the examined deceptive tendencies, which suggest to deepen the role of EM as a risk factor for drug relapse and treatment success.